Dominance of the GI-19 genotype and genomic characterization of the S1 gene in avian infectious bronchitis virus from 2020 to 2024 - Xiaozhen Guo; Cunxia Liu; Feng Hu; Liping Liu; Tong Zhu; Yuehua Gao; Zhongyin Lin; Huaiying Xu; Bing Huang; Zhuoming Qin; Xiuli Ma (Frontiers in Cellular and Infection Microbiology, 2025)
The continuous emergence of avian infectious bronchitis virus (IBV) variants poses a critical threat to poultry health and productivity in China. In this study, we conducted comprehensive genetic and antigenic analyses of IBV strains isolated in our laboratory between 2020 and 2024. A total of 94 IBV isolates were sequenced for the S1 gene, revealing widespread nucleotide insertions, deletions, and mutations. Phylogenetic analysis indicated that GI-19 was the predominant genotype (70.21%), followed by GI-13 (21.28%). Recombination analysis using RDP 5.42 identified 14 recombinant strains, primarily GI-13/GI-22 (50%), GI-19/GI-7 (28.6%), and GI-19/GI-22 (21.4%), which were further confirmed using Simplot. Glycosylation analysis revealed that all isolates possessed 14 to18 N-glycosylation sites, whereas only the SDJN3/23 strain contained an O-glycosylation site (position 416). Novel cleavage site motifs (HRRKR, HRHRR, RRFRR) were identified in GI-19 strains, diverging from the canonical HRRRR. The evolutionary rate calculated via BEAST software, was 1.98 × 10-4 substitutions/site/year. Serum neutralization assays demonstrated that GI-19 recombinants exhibited partial one-way cross-protection against GI-1, GI-13, and GI-22 genotypes (titer ≥ 1:32), but reciprocal neutralization was limited. Overall, we systematically characterized the genetic diversity and antigenic evolution of the currently circulating IBV strains in China, emphasizing the critical demand for genotype-specific vaccine development and dynamic surveillance systems to counteract viral immune escape.